Improving the Effectiveness of Learning to Learn to Fables Using Visual Audio Media in Class VII-1 Students of SMP Kristen Saparua - Kundre, Esterlina; Sasabone, Carolina; Somelok, Grace (Mirlam: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
This study uses Classroom Action Research (CAR). With the title Increasing the Effectiveness of Learning to Listen to Fables Using Audio Visual Media in Class VII-1 Students of Saparua Christian Middle School. The sample in this study was 23 people from class VII-1. Data collection techniques used are observation, interviews, questionnaires, assignments. The instruments used were interview guides, observation sheets, tests and questionnaires. There are three data analysis techniques, namely data reduction, data exposure and inference. The results showed that in the first cycle, there were 18 students who had not reached the KKM standard, while the percentage of students who reached the KKM standard was 5 students (26.08%) out of 23 students with a total score of 952.5 and the research results in the first cycle II who did not reach the KKM standard were 6 students, while students who achieved the KKM were 17 students (73.91%) of the 23 students with a total score of 1.555. Based on the results of the study, it can be concluded that the results of learning to listen to fables have been able to reach the minimum limit of learning completeness categorized as very satisfying.